Vitamin D status in exclusively breastfed infants and their mothers - Kumaran, C. R. Vignesh; Sivakumar, K. V.; Kumar, R. Suresh (International Journal of Contemporary Pediatrics, 2021)
Background: The prevalence of hypovitaminosis D in exclusively breastfed infants was found to be 82%, 52% and 20 % from UAE, Pakistan and China respectively but there is a paucity of data from India regarding the same. Methods: Prevalence of subclinical Hypovitaminosis D in exclusive breastfed babies and their mothers. This study was a descriptive study conducted among breastfed infants and their mothers to reconnoitre the vitamin D level status. All exclusively breast fed healthy term babies with birth weight >2.5 kg who are less than 6 months of age and its mothers. The existence of correlation in the mean vitamin D level between the exclusively breastfed mothers and its infants. Results: The infants status of vitamin D deficiency and insufficient was 91.9% and 8.1% respectively. The mothers status of vitamin D deficiency and insufficient was 78.3% and 21.7% respectively. Conclusions: Hypovitaminosis D was highly prevalent among mothers living in tropical area irrespective of diet habits or socioeconomic group. There was a significant positive correlation in the mean Vitamin D level of the mothers and their exclusively breastfed infants.